Research on performances of single sideband modulated OFDM signals in ROF optical transmission system - LEI Xiao-yan1; CHEN Lin1; DONG Ze1; CAO Zi-zheng1; LU Jia1; YU Jian-jun1 (Tongxin xuebao)
A novel OFDM-ROF system using single sideband modulation technology in radio-over-fiber system to generate optical wave was proposed and experimentally demonstrated.The 2Gbit/s OFDM signal and a 10GHz RF clock were mixed.The mixed signals were applied to drive a double-arm intensity modulator to generate a single sideband signal which transmitted to base station（BS） over fiber and broadcasted by antenna after the optical OFDM signal was converted into electrical OFDM signal.The experiment results show that in 10GHz-ROF system,a 2Gbit/s OFDM signal transmitted over 200km SMF without wireless broadcasting only has 1dB power penalty.After being only transmitted over 8m wireless air distance it has 0.3dB power penalty.When the signal transmitted over both 200km SMF and wireless air distance of 8m,also can obtain a clear received constellation in the experiment.